The Euro Crisis in the Media: Journalistic Coverage of Economic Crisis and European Institutions - Picard, Robert G (Reuters Institute for the Study of Journalism, 2015)
The Euro Crisis produced the most significant challenge to European integration in 60 years--testing the structures and powers of the European Union and the Eurozone and threatening the common currency. This book explores how the financial and political crisis was portrayed in the European press and the implications of that coverage on public understanding of the developments, their causes, responsibilities for addressing the crisis, the roles and effectiveness of European institutions, and the implications for European integration and identity. It addresses factors that shaped news and analysis, the roles of European leaders, and the extent to which national and pan-European debates over the crisis occurred. In doing so, it provides a clear and readable explanation of what the portrayals tell us about Europe and European integration in the early twenty-first century.